Analisis Yuridis Peran OJK dalam Melakukan Perlindungan Hukum Korban Pinjaman Online Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 77/Pojk.1/2016 - Mayrendra, Randika Theo; Suryono, Ahmad (Indonesian Journal Publisher, 2023)
OJK is an independent institution that has the authority to regulate and supervise financial services activities in the banking sector, capital markets sector and non-bank financial industry (IKNB) sector. OJK itself was formed and based on the principles of good governance including independence, accountability, responsibility, transparency and fairness, which institutionally OJK is not part of the government's authority. The OJK institution itself was born with law no. 21 of 2011 concerning the OJK Institution which came into effect on January 1 2013, which has the authority to regulate and supervise financial institutions, especially banking in Indonesia, as stated in Law No. 21 of 2011 Article 5. On October 20 2021, the online loan case went viral. illegal or legal, starting from debt collectors from illegal loans who start collecting on the 3rd day of the payment deadline to hacking the victim's cellphone to get contacts of the victim's family or people closest to them, so that the OJK often blocks illegal online loan applications on Playstore. This article uses the statue approach method and conceptual approach to legal research which examines laws and regulations relating to legal issues and provides an analytical perspective on solving problems in legal research seen from the aspect of the legal concepts behind them. The research results found that only legal loans can be reported to the OJK while illegal online loans can be reported to the police